A Correlation between the Kinetic and Thermodynamic Adsorption Characteristics of an Optical Brightener on a Pulp Surface - Greta Radeva; Stefka Veleva; Eva Valcheva (Adsorption Science & Technology)
An attempt to find a correlation between the kinetic and thermodynamic terms (e.g. activation energy, pre-exponential factor, isosteric heat, entropy, etc.) of the chemisorption process involved in a commercial optical brightener/pulp system is presented. A linear inter-relationship between the kinetic and thermodynamic characteristics of the system was found. Based on the coefficients obtained in the thermodynamic investigation of the adsorption process, it was possible to calculate the kinetic coefficient of the surface inhomogeneity. The use of both a model employing uniformly inhomogeneous surfaces and an approach involving all the kinetic and thermodynamic data was confirmed by the results obtained.